Financial Deepening in the CFA Franc Zone : The Role of Institutions - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 2009)
During the 1980s and early 1990s many Sub-Saharan African (SSA) countries undertook reforms to promote financial sector deepening. Nevertheless, financial sectors in SSA countries remain among the shallowest in the world and, within Sub-Saharan Africa, financial depth in the CFA franc zone is even more limited. This paper sets out to investigate empirically factors that may explain why financial depth in the CFA franc zone is shallower than in the rest of SSA using panel data for a sample of 40 countries for 1992-2006. The results indicate that the gap in financial development between the CFA franc zone countries and the rest of SSA can be explained by differences in institutional quality (e.g., availability of credit information, and strength and enforcement of property rights), variables that policy makers can influence.